Profiling Calon Mahasiswa Program Studi Informatika Menggunakan Decision Tree - Rizki Hesananda; Ninuk Wiliani; Latifah (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2020)
Prospective student data can be used as important information for academic community, therefore proper data management needed to process it. This research uses the prospective student throught the 2020 APERTI scholarship path as the basis for the classification of prospective students which wasa previously done manually using Microsoft Excel so that the classification process is not optimal. The process of identifying profiles uses data mining to determine marketing plans and pattern of prospective students with a profile classification process as well as offering recommendations for them. This research used decision tree (C4.5). The attributes used for the classification process are father’s job, mother’s job, gender, school type, major and the choice of the chosen study program. The result of this research can be used to help sort out prospective students according to the informatics study program.